Xunzi's concern for yu (desire) and ritual approaches for its moral transformation - Zhou,Yalin (Nanyang Technological University, 2024)
This dissertation focuses on Xunzi’s moral concern for yu 欲 (desire) with three primary aims: (1) to conceptualize Xunzi’s notion of yu; (2) to investigate and add a new understanding of what Xunzi conceives as the badness in uncultivated desires and the goodness in cultivated desires; (3) and to illustrate the embodied and sociocultural approaches/dimensions of rituals transforming problematic inborn desires and generating moral desires. For the first aim, I argue that Xunzi’s notion of yu could be conceived as a feeling that it is imperative or even compulsive to pursue something on the expectation that doing so will yield pleasure for the desirer. One’s pleasure-based liking is not merely painted by joy but a configuration of the more variable affective experiences, including the feeling of an 安 (security; at ease) and the feeling of comfort in fortunes and anxiety in misfortunes, and involves the higher and lower pleasures; and the potent force of wanting is normatively grounded in the general goal of living a truly happy life. For the second aim, while most readers explain the badness of inborn desires with problematic objects and chaotic social consequences, I propose that Xunzi also has another point in mind: the felt quality of desires. The leading felt quality of desires could be distinguished by the qing 情 (emotions; feelings) that go along with it because Xunzi believes that desires are responses of qing, with the appearance of qing being fundamentally associated with qi 氣 (energy substance) and bodily experiences. The felt quality of uncultivated desires is bad in that they feel so abrupt, uncontrollable, and inconsistent that they not only create a kind of internal misery and ordinary feelings of worry for the desirer but also make the desirer callous of the interests of others. The bad felt quality is primarily rooted in its corrupted and disordered embodied affective experience. By comparison, cultivated desires feel better because they feel smooth, controllable, consistent, and thereby more enjoyable. For the third aim, compared with a large volume of Xunzi scholarship that has described the xin 心 (heart-mind) as a decisive factor in cultivating an affective love for morality and Dao, the less mindful and less individualistic approaches of desire and desire transformation have not being illustrated sufficiently. The embodied and the sociocultural perspectives could supplement or complement some prior works on how a bad-natured self could develop a love for Dao and propriety. One main argument is that for Xunzi, it is possible to feel the higher pleasure of propriety and Dao, with its content being primarily sensory or bodily. The approach is to give a proper pattern to the feelings of desire pertaining to one’s natural and common desires. Specifically, by practicing rituals as bodily techniques and physiological guides in everyday living (e.g., eating, dressing, dwelling), one is led to feel the heightened pleasure of propriety embedded in an appropriate and beautiful pattern of desiring and enjoying multiple humane goods. In this process, one’s sensory perceptions and body are attuned and improved to a higher level so that the perverted and disordered appearances of yu-related feelings and the originally abrupt and irregular manner of acting/performing become gradually disassociated with pleasure. To complement some current discussions of moral deliberation as a crucial approach for desire transformation, this dissertation also argues that it is essential to consider the sociocultural self, namely, seeing oneself as a bearer of specific roles in a larger community characterized by role-based rituals and division. By the approach of habituating in a ritualized community (zhu cuo xi su 注错習俗), one is led to develop and construct a sociocultural self, and thereby understand the otherwise uninterpreted desires from a quasi-moral perspective, focus on the specified interests in accord with one’s social role, and acquire the taste/ability to have one’s feeling for security and honor anchored in morality and the Dao.